(untitled) (Research, Society and Development, 2022)
Objective: To address the use of SGLT-2i for the prevention of cardiovascular events in patients with type 2 diabetes mellitus. Materials and Methods: This is a descriptive, integrative literature review. Literary searches took place from articles indexed in SciELO, PubMed and MEDLINE, the latter via BVS, in english between 2017 and 2022 (last 5 years). To perform the searches, terms in DeSC and MeSH were considered in association with Boolean operators: (Diabetes Mellitus, Type 2) AND (Cardiovascular Diseases) AND (Prevention) AND (Sodium-Glucose Transporter 2 Inhibitors). Results: Overall, study analyzes revealed benefits in a variety of cardiovascular outcomes. SGLT-2i reduced MACE, the composite of (cardiovascular death and ICH), non-fatal myocardial infarction, ICH or HF, cardiovascular death, all-cause death, but without efficacy on cerebrovascular events. Analyzing the cardiovascular results, protection in renal events was found, with a decrease in the progression of albuminuria, renal failure and renal compounds. Checking the subgroups of patients, SGLT-2i decreased several cardiovascular events, mainly in individuals with HF, CVD, reduced renal function and CKD, noting in the latter, improvements in renal events. Comparisons of SGLT-2i versus other antidiabetic agents were performed, in which lower risks were observed in different cardiovascular and renal events with SGLT-2i. Conclusion: In fact, prevention in several cardiovascular outcomes was proven with SGLT-2i in patients with type 2 diabetes mellitus.